Experimental investigation of concrete-filled double-skin stainless steel tubular beam-columns. (September 2022) - Zhou, Feng; Li, Yingfei; Dong, Baiping
Abstract: This paper presents an experimental investigation of the hysteretic behavior of concrete-filled double-skin stainless steel tubular (CFDSST) beam-columns with circular hollow section (CHS) outer and inner. A total of 18 specimens were designed and tested under constant axial compressive load and cyclically increasing flexural load to investigate the structural performance of the composite beam-columns and evaluate the effects of varied design parameters, including the thicknesses of the CHS outer and inner and concrete strength, on the performance of the hysteretic behavior of the CFDSST beam-columns. Both of the lateral load ( P ) versus lateral displacement ( Δ ) hysteresis response and moment ( M ) versus drift angel ( θ ) hysteresis response were obtained. Based on which, the failure mechanism, ductility, energy dissipation capacity, stiffness degradation, and ultimate strength of the specimens were investigated. The results show that the specimens failed in a ductile mechanism features bulge and rupture at the bottom of the CHS outer, unimpaired CHS inner, and local concrete crush, demonstrating the combined effect of the stainless tubes with the concrete. All of the specimens showed high level of ductility and energy dissipation capacity. Finally, comparisons of ultimate bending moments of the beam-columns between the test results and predictions from the existing design codes and design method demonstrate the deign codes underestimates bending moment strength of the CFDSST beam-columns. Highlights: The failure mechanism of CFDSST beam-columns under cyclically flexural load is revealed. The effects of design parameters on ductility, energy consumption capacity, and ultimate moment capacity are evaluated. The accuracy of existing design method for ultimate moment capacity prediction is validated. The need to consider strain-hardening of stainless steel and confining effect of tubes on concrete in design are demonstrated.